Pertumbuhan dan Kelangsungan Hidup Larva Ikan Patin Siam (Pangasianodon Hypophthalmus .F.) dengan Intensitas Cahaya yang Berbeda - Try Noprianto; Muhammad Sugihartono; M Yusuf Arifin (Universitas Batangahari Jambi, 2022)
One of the influencing external factors is environmental conditions. Light is part of the environment that has a role in life in water. The study of light intensity on the rearing of Siamese catfish (P. hypopthalmus .F.) Larvae aged 1 day has not been comprehensively carried out in terms of its impact on growth and survival. The purpose of this study was to examine the effect of differences in light intensity on growth and survival of Siamese catfish (P. hypopthalmus .F.) Larvae. The research design was carried out using a Completely Randomized Design (CRD) model with 4 (four) treatments and 3 (three) replications, including without light intensity 0 lx (A), light intensity 61.4 x 10 lx (B), light intensity 109 , 7 x 10 lx (C) and light intensity 22.3 x 100 lx (D). The difference in light intensity tested in this study affected the growth and survival of Siamese catfish (P. hypopthalmus .F.) Larvae. The best light intensity in this study was found in treatment B, namely the provision of light intensity 61.4 x 10 Lx with the value of absolute length growth, absolute weight growth, daily growth rate and the best feed efficiency compared to other treatments.